Photoelectron spectroscopy on single crystals of organic semiconductors: experimental electronic band structure for optoelectronic properties. Issue 27 (19th May 2020) - Nakayama, Yasuo; Kera, Satoshi; Ueno, Nobuo
Abstract : Methodologies and experimental achievements for exploration into electronic band structures of organic semiconductor and hybrid perovskite single crystals are reviewed. Abstract : Modern opto-electronics technologies are built on the basis of fundamental knowledge about electronic properties of semiconductor materials, which can be attained through accurate analyses made on single crystals of the materials as standard samples. In the cases of organic semiconductor materials, although technical difficulties have obstructed direct measurements of electronic properties in the organic semiconductor single crystals by photoelectron spectroscopy, recent advances in the experimental methodologies have been opening a route for accessing their electronic bands, defect-induced "gap states", and core levels by using single crystals of the organic semiconductors at higher accuracy and precision. In this review, we summarize recent achievements for the exploration into the electronic structures on organic semiconductor single crystals. The energy-momentum dispersion relations of holes obtained by the angle-resolved ultraviolet photoelectron spectroscopy (ARUPS) measurements are mainly focused, which allow one to deduce one of the most essential properties dominating the charge carrier transport, that is, the effective mass of a quasi-particle, namely dressed charge, and impact of electron–phonon coupling to the band structure. We describe theoretical bases of the ARUPS methodology and peculiar know-hows for adopting this technique to the molecular single crystal samples, which prone to be charged up upon photoelectron emission because they are good electrical insulator.